What Can We Learn About Aggression From What Adolescents Consider Important in Life? The Contribution of Values Theory to Aggression Research. (14th October 2019) - Benish‐Weisman, Maya
Abstract: Values are abstract goals that serve as guiding principles in people's lives. Schwartz's theory (1992) offers a comprehensive framework to understand what motivates human behavior. It classifies people's broad motivations into a system of values organized in a circumplex structure. In this article, I explain how recent findings from studies of values can add to our knowledge of what motivates adolescents to behave aggressively. For example, during adolescence, values emphasizing caring for others and maintaining social norms relate negatively to aggression, whereas values promoting self‐focus and pursuing new experiences and stimulation relate to aggressive acts. I also discuss the potentially protective role of some values, the mechanisms mediating the relations between values and aggression, and the relations between values and aggression over time. Finally, I suggest new directions for research and discuss the importance of including values in interventions to prevent aggression.